Morphological Assessment of MACI Grafts in Patients with Revision Surgery and Total Joint Arthroplasty. (December 2021) - Beck, Aswin; Wood, David; Vertullo, Christopher J.; Ebert, Jay; Janes, Greg; Sullivan, Martin; Zheng, Ming-Hao
Objective: To compare the histological and immunohistochemical characteristics of matrix-assisted chondrocyte implantation (MACI) grafts between patients with revision surgery and patients with total joint arthroplasty. Methods: Biopsies of MACI grafts from patients with revision and total joint arthroplasty. The graft tissue characteristics and subchondral bone were examined by qualitative histology, ICRS (International Cartilage Repair Society) II scoring and semiquantitative immunohistochemistry using antibodies specific to type I and type II collagen. Results: A total of 31 biopsies were available, 10 undergoing total knee arthroplasty (TKA) and 21 patients undergoing revision surgery. Patients in the clinically failed group were significantly older (46.3 years) than patients in the revision group (36.6 years) ( P = 0.007). Histologically, the predominant tissue in both groups was of fibrocartilaginous nature, although a higher percentage of specimens in the revision group contained a hyaline-like repair tissue. The percentages of type I collagen (52.9% and 61.0%) and type II collagen (66.3% and 42.2%) were not significantly different between clinically failed and revised MACI, respectively. The talar dome contained the best and patella the worst repair tissue. Subchondral bone pathology was present in all clinically failed patients and consisted of bone marrow lesions, including edema, necrosis and fibrosis, intralesional osteophyte formation, subchondral bone plate elevation, intralesional osteophyte formation, subchondral bone cyst formation, or combinations thereof. Conclusions: MACI grafts in patients with revision and total joint arthroplasty were predominantly fibrocartilage in repair type, did not differ in composition and were histologically dissimilar to healthy cartilage. Clinically failed cases showed evidence of osteochondral unit failure, rather than merely cartilage repair tissue failure. The role of the subchondral bone in relation to pain and failure and the pathogenesis warrants further investigation.